The Development of Pre-School Children’s Feeling of Mode Applying the Intonations ofLithuanian Folk Songs - Šečkuvienė, Henrika (Acta Paedagogica Vilnensia, 2003)
The engagement of a child into meaningful musical activity in pre-school age is important in taking over and developing national culture. In the early age, when a child learns to master primary vocabulary of intonation, it is important not only to properly select and systematize musical intonations, which helps a child to feel the mode sooner and easier, but while developing a child's musicality and enriching his personality, the artistic emotional meaning of those intonations is very important too. Therefore the intonations of folk songs are most suitable for development of musical language in the primary level. The goal of this article is to analyse the efficiency of the use of Lithuanian folk songs intonations developing pre-school age children's feeling of mode. The results of the research indicated that in most of the children feeling of mode is of low and average level. Summarizing the results of the research it was concluded that the ability of pre-school) age children to feel the mode successfully develops when applying the children's musical abilities complex development model and when educational material is based on the intonations of Lithuanian folk songs.
Keywords: pre-school age; national culture; folk songs; musical activity; mode